Design and synthesis of β-strand-fixed peptides inhibiting aggregation of amyloid β-protein. Issue 18 (15th September 2020) - Tanaka, Fumiya; Shibata, Kana; Monobe, Yoko; Akagi, Ken-ichi; Masuda, Yuichi
Graphical abstract: Abstract: Aggregation of 42-residue amyloid β-protein (Aβ42) can be prevented by β-sheet breaker peptides (BSBps) homologous to LVFFA residues, which are included in a β-sheet region of Aβ42 aggregates. To enhance the affinity of BSBps to the Aβ42 aggregates, we designed and synthesized β-strand-fixed peptides (BSFps) whose side chains were cross-linked by ring closing metathesis. Conformation analysis verified that the designed peptides could be fixed in β-strand conformation. Among the synthesized pentapeptides, 1 and 12, whose side chains of 2nd and 4th residues were cross-linked, significantly inhibited the aggregation of Aβ42. This suggested that β-strand-fixation of BSBps could enhance their inhibitory activity against the Aβ42 aggregation. However, pentapeptides 1 and 12 had little effect on morphology of Aβ42 aggregates (fibrils) and neurotoxicity of Aβ42 against SH-SY5Y cells.